PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA PADA PT. PLN (PERSERO) DISTRIBUSI JAWA TIMUR - AUDINA SITO P, VISCA (Jurnal Ilmu Manajemen (JIM), 2018)
PT. PLN (Persero) Distribusi Jawa Timur is one of the main implementing unit under PT. PLN (Persero) is engaged in the distribution and sale of electric power in East Java. Achievement of organizational performance can be supported by the application of total quality management within the company. Factors that can affect organizational performance are customer focus, top management, employee engagement and empowerment, training education, and continuous improvement. This study aims to examine and analyze the effect of total quality management implementation on organizational performance at PT. PLN (Persero) Distribusi Jawa Timur. Type of research with method of quantitative approach. The sample in this study amounted to 83 respondents PT. PLN (Persero) Distribusi Jawa Timur with sampling technique that is slovin method. Statistical analysis used in this study is multiple linear regression with the help of SPSS Version 21 program. The result of this study explains the focus of customer positively influence to organizational performance, top management have positive effect on organizational performance, involvement and empowerment have positive effect to organizational performance, training education have positive effect to organizational performance, continuous improvement have positive effect to organizational performance, total quality management simultaneously have a positive effect on organizational performance. Keywords : total quality management, organizational performance.